GaN‐on‐Si(100): Epitaxy of Single‐Crystalline GaN Film on CMOS‐Compatible Si(100) Substrate Buffered by Graphene (Adv. Funct. Mater. 42/2019). (15th October 2019) - Feng, Yuxia; Yang, Xuelin; Zhang, Zhihong; Kang, Duan; Zhang, Jie; Liu, Kaihui; Li, Xinzheng; Shen, Jianfei; Liu, Fang; Wang, Tao; Ji, Panfeng; Xu, Fujun; et al.
Abstract : In article number1905056, Xuelin Yang, Kaihui Liu, Bo Shen, and co‐workers achieve the epitaxy of single‐crystalline gallium nitride (GaN) film on a complementary metal‐oxide‐semiconductor‐compatible Si(100) substrate by applying a one‐atom‐thick single‐crystalline graphene buffer layer. The monolayer graphene provides an in‐plane driving force for the uniform alignment of nitrides domains. This apppoach can also enable the growth of wafer‐scale hexagonal single‐crystalline films on amorphous or flexible substrates.